CHARACTERISTIC OF LANDSLIDE IN SEULAWAH ROAD KM 80-81, BASED ON GEOPHYSICAL DATA AND GEOTECHNICAL PARAMETERS - Zul Fadhli; Etian Wirsya; Yurda Marvita; Layna Miska; Muhammad Syukri; Khalif AlFaiz (Institut Teknologi Sepuluh Nopember, 2025)
This study identifies the sliding plane along the Seulawah Road (km 80-81), Muara Tiga, Pidie Regency, where a massive landslide occurred in 2023. Using the Multichannel Analysis Surface Waves (MASW) method, this research integrates shear wave velocity (Vs) data with N-SPT values and soil-bearing capacity to analyze subsurface characteristics. The study aims to characterize the sliding plane and associated weak zones by combining geophysical and geotechnical approaches. The interpretation reveals the existence of a sliding mass layer consisting of sandy gravel material at a depth of 1-3 meters with a Vs value in the range of 60-150 m/s. Underneath that, the sliding plane is found, which is interpreted as a stiff clay layer with the Vs value in the range of 155-450 m/s at a depth of 6-10 meters. The soil bearing capacity also aligned with these findings with the 20-80 kN/m2 value in the very loose sandy gravel layer. The soil-bearing capacity of the sliding plane, the clay layer, is 250-311 kN/m2. Those findings provide valuable insights into landslide characteristics and highlight the dynamic instability of the sliding plane. Moreover, this study contributes to assessing critical parameters for future reconstruction and road maintenance, offering an essential reference for landslide-prone regions.